Menakar Kesiapan Petani Muda di Kota Tasikmalaya dalam Mengadopsi Teknologi Pertanian - Wilva Ramadayanti; Adenty Oktavianty; Andena Nur Hikmatunnisa; Aini Dewi Maryan; D Yadi Heryadi (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Farmer regeneration is a strategic element in achieving sustainable agricultural development, especially amid the overall decline in the farming population. This study aims to identify the demographic trends of young farmers and examine their readiness in adopting agricultural technology in Tasikmalaya City. The research employs a descriptive qualitative approach using secondary data obtained from the Central Bureau of Statistics, the Ministry of Agriculture, and various scientific literature. The findings reveal that despite the overall decrease in the number of farmers, the number of young farmers has increased in recent years, indicating potential for regeneration in the agricultural sector. Young farmers tend to be more open to innovation and possess relatively strong digital literacy; however, the adoption of agricultural technology remains limited to specific aspects and has not fully integrated into the entire production process. The main challenges include limited access to capital, underdeveloped digital infrastructure, and a lack of technical training and mentoring. Therefore, comprehensive policy interventions are necessary, including strengthening farmer regeneration policies, improving supporting infrastructure, and promoting community-based mentoring to accelerate the adoption of agricultural technology among young generations.